THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN INCREASING SPEAKING ACHIEVEMENT AND SELF-CONFIDENCE OF ELEVENTH GRADE STUDENTS OF SMK NEGERI 1 SANGA DESA - Davis Davis; Tahrun Tahrun (Universitas PGRI Palembang, 2022)
This Objectives of the study were to find out: (1) whether or not Project-Based Learning (PBL) could make a significant difference in increasing both students’ speaking achievement and self-confidence, and (2) the contribution of PBL towards both students’ speaking achievement and self-confidence. This study employs factorial design where the students were equally divided into two groups. The results showed that (1) there was a significant difference both in speaking achievement (t=0.581, p<.000) and self-confidence (t=7.968,p<.000) of the experimental group after being taught using PBL, (2) there was also a significant difference between experimental and control groups both in speaking ability (t=2.307, p<.027) and self-confidence (t=3.595, p<.001) , (3) the contribution of PBL to the students’ speaking achievement was 99.7% and to self-confidence was 92.7%. In conclusion, PBL could be considered as an effective method in teaching speaking and in increasing students’ self-confidence.